Reducing time to analgesia in the emergency department using a nurse-initiated pain protocol: A before-and-after study - Finn, Judith; Rae, A.; Gibson, N.; Swift, R.; Watters, T.; Jacobs, Ian (eContent Management, 2012)
Suboptimal management of pain in emergency departments (EDs) remains a problem, despite having been first described over two decades ago. A 'before-and-after' intervention study (with a historical control) was undertaken in one Western Australian tertiary hospital ED to test the effect of a 'nurse-initiated pain protocol' (NIPP) intervention. A total of 889 adult patients were included: 144 in the control group and 745 in the intervention group. Patients in the intervention group were: More likely to have a pain score recorded than those in the control group; have reduced median time to the first pain score; and reduced time to analgesia. The statistically significant reduction in both time to pain score and time to analgesia remained, even when adjusted by age and sex. Whilst we demonstrated the safety and efficacy of a NIPP in ED, an unacceptable proportion of patients continued to have inadequate pain relief.